Delphi cookbook : 50 hands-on recipes to master the power of Delphi for cross-platform and mobile development on Windows, Mac OS X, Android, and iOS /: 50 hands-on recipes to master the power of Delphi for cross-platform and mobile development on Windows, Mac OS X, Android, and iOS. (2014) - Teti, Daniele
No abstract available